Estudo da eficiência da realcalinização na repassivação de armaduras - Carvalho, Mariane Rodrigues de (2018)
Reinforcement corrosion triggered by concrete carbonation is one of the main degradation mechanisms of reinforced concrete structures. The realkalisation treatment is one of the methods applied to recover the alkalinity condition of the cementitious matrix and, consequently, to meet the possible reinforcement repassivation without any significant destructive procedure to the structure. The present work sought to analyze the behavior of reinforcement with different degrees of corrosion, submitted to the realkalisation treatment. For this purpose, 6.3 mm diameter reinforcement bars were immersed into cells divided into two groups (solution 01 and solution 02), each group with both different solutions and corrosion rate conditions. The first group (solution 01) contained a saturated solution of calcium hydroxide and the second group (solution 02) contained a mixed saturated solution of calcium hydroxide, potassium hydroxide and sodium hydroxide. These solutions were used to simulate the liquid phase of the concrete. After a period of twenty days (average), these solutions were carbonated with carbon dioxide gas (CO2) until reaching a pH close to 8. Then, solution 01 cells remained in laboratory environment for 7, 28, 40, 70 and 90 days, while solution 02 cells remained for 7, 14, 28, 56 and 90 days, in order to meet different corrosion degrees. Afterwards, the carbonated solutions were realkalised by changing the solutions for new ones (no CO2). The steel bars were monitored throughout these periods by electrochemical measurements using the linear polarization resistance technique. Such measurements showed the moments in which reinforcements bars were depassivated, the increase of the corrosion current, and the corrosion potential decay, as well as the moments in which these parameters changed their behavior due to the realkalisation. Results showed that longer exposure to carbonated media made it difficult to the reinforcement repassivation occurs.